Garden story inspiring spaces, healing places - Reifenberger, Bill.; Frischkorn, Rebecca; Rainey, Reuben M.; Silverthorn Films; PBS Home Video ([S.l.] : Distributed by PBS Home Video, 2008)
This ten part series, filmed across America, challenges common perceptions of what defines a garden and explores the many different roles that gardens play in today's world.
Disc 1: The garden as muse ; The garden as environmental stewardship ; The garden as exploration in creativity ; The garden as classroom ; The garden as teacher ; The garden as catalyst for community -- disc 2. The garden as healer ; The garden as public park ; The garden as autobiography ; The garden as protector of the planet.
Host, Rebecca Frischkorn.
Originally broadcast in 2008.
DVD ; NTSC region 1 ; widescreen ; English: stereo.
Keywords: Gardens; Gardens -- Social aspects; Television programs -- United States; Documentary television programs; Video recordings for the hearing impaired; Nonfiction television programs